2019
DOI: 10.1038/s41598-019-44243-x
|View full text |Cite
|
Sign up to set email alerts
|

Revealing How Topography of Surface Microstructures Alters Capillary Spreading

Abstract: Wetting phenomena, i.e. the spreading of a liquid over a dry solid surface, are important for understanding how plants and insects imbibe water and moisture and for miniaturization in chemistry and biotechnology, among other examples. They pose fundamental challenges and possibilities, especially in dynamic situations. The surface chemistry and micro-scale roughness may determine the macroscopic spreading flow. The question here is how dynamic wetting depends on the topography of the substrate, i.e. the actual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 44 publications
(63 reference statements)
1
13
0
Order By: Relevance
“…This is consistent with past works that demonstrated that roughness has a small effect on the maximum spreading at high We and Re numbers 48,49 . Other works, also in agreement with our findings, have demonstrated that spreading is more affected by roughness on hydrophilic substrates than on hydrophobic ones 23,50,51 . At U 0 = 2.05 m/s, the smallest spreading diameter was found on the Glaco covered smooth glass (D m = 2.87), while the (uncoated) smooth glass showed the largest spreading diameter (D m = 3.59).…”
Section: Resultssupporting
confidence: 94%
“…This is consistent with past works that demonstrated that roughness has a small effect on the maximum spreading at high We and Re numbers 48,49 . Other works, also in agreement with our findings, have demonstrated that spreading is more affected by roughness on hydrophilic substrates than on hydrophobic ones 23,50,51 . At U 0 = 2.05 m/s, the smallest spreading diameter was found on the Glaco covered smooth glass (D m = 2.87), while the (uncoated) smooth glass showed the largest spreading diameter (D m = 3.59).…”
Section: Resultssupporting
confidence: 94%
“…In this regime, we assume Young's force is driving the contact line and the line friction is the resistive force. Assuming that wetting resistance for spread-and-leap is dominated by line friction, we can develop a theoretical model of the contact-line velocity based on the Navier-Stokes-Cahn-Hilliard equations 35,36 ,…”
Section: A Model For Spread-and-leap Regimementioning
confidence: 99%
“…We assume that Eq. ( 7) is a valid model of liquid front at any surface point 35,36 . Considering the local dynamic contact angle and velocity, we sum up the time to pass sections i = 1, .…”
Section: A Model For Spread-and-leap Regimementioning
confidence: 99%
“…It provides a means to account for the energy dissipation rate ∼ µ f U 2 at the contact line (here U is a contact line velocity). The contact line friction has been used in models of moving contact lines [25,30] and can be measured experimentally [24,28,29] or by parameter fitting of numerical simulations to experiments [23,31]. The values of the line friction parameter in previous studies are in the order of 0.1 Pa•s for water and increase in proportion to the square root of the liquid viscosity up to ∼ 1 Pa•s [23,24,27].…”
Section: Introductionmentioning
confidence: 99%
“…For non-smooth surfaces, one may define an effective line friction parameter that takes geometric surface details into account. Based on this parameter, one may normalize time such that the spreading curves of different droplets on microstructures exhibit nearly the same scaling [21,31,32].…”
Section: Introductionmentioning
confidence: 99%